2014
DOI: 10.1089/neu.2013.3212
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pituitary Hormone Dysfunction, Metabolic Syndrome, and Impaired Quality of Life in Retired Professional Football Players: A Prospective Study

Abstract: Hypopituitarism is common after moderate and severe traumatic brain injury (TBI). Herein, we address the association between mild TBI (mTBI) and pituitary and metabolic function in retired football players. Retirees 30-65 years of age, with one or more years of National Football League (NFL) play and poor quality of life (QoL) based on Short Form 36 (SF-36) Mental Component Score (MCS) were prospectively enrolled. Pituitary hormonal and metabolic syndrome (MetS) testing was performed. Using a glucagon stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 88 publications
1
52
3
1
Order By: Relevance
“…The estimated burden of long-term disability related to TBI is even greater, affecting approximately 5.3 million individuals in the United States (1). Furthermore, it is likely that TBI is underreported, particularly among patients with mild TBI or those with sportsrelated injuries, many of whom may suffer repeated head trauma (3). In the acute phase, access to health care may be limited in war zones, which may further contribute to underreporting of TBI in these settings.…”
Section: Epidemiologymentioning
confidence: 99%
“…The estimated burden of long-term disability related to TBI is even greater, affecting approximately 5.3 million individuals in the United States (1). Furthermore, it is likely that TBI is underreported, particularly among patients with mild TBI or those with sportsrelated injuries, many of whom may suffer repeated head trauma (3). In the acute phase, access to health care may be limited in war zones, which may further contribute to underreporting of TBI in these settings.…”
Section: Epidemiologymentioning
confidence: 99%
“…We shall now discuss why exactly TBI-induced hormone deficiency in athletes is cause for concern, and how this concern can be lessened. 3 Nevertheless, in a recent prospective study Kelly et al [44] examined the relationship between hormone dysfunction, concussion, and quality of life in retired NFL players. Surprisingly, they did not find that the amount of NFL games played and the number of reported concussions correlated with an increase in hormone dysfunction.…”
Section: Traumatic Brain Injury Hormone Levels and Sportsmentioning
confidence: 99%
“…For instance, the sample size of NFL players with hormone dysfunction was significantly lower than the sampe size of NFL players without hormone dysfunction. Additionally, it is notoriously difficult to monitor the concussion history and steroid use history in athletes [44].…”
Section: Traumatic Brain Injury Hormone Levels and Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…While that study had some shortcomings, we believe its main message likely is correct given that the finding persists in more diverse populations of football players as they mature in that sport, through high school [25], college [30] and even at the professional level [4]. Other serious health risks appear in football players at unusually young ages; one study found metabolic syndrome in nearly 20% of collegiate football players [30], and studies on professionals and retired pros found even-more severe health problems [14,24,29], despite those athletes presumably having the best access to trainers, dietary advice, and the ability to focus full-time on physical fitness. Metabolic syndrome, obesity, and carotid plaques simply do not come up in conversations about hockey, soccer, and basketball, and these findings cast additional doubt on the idea that football is an activity that improves the health of young men.…”
mentioning
confidence: 98%